2016
DOI: 10.1007/s11250-016-1153-z
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of swine influenza in intensive and extensive farms in the northeastern region of the state of São Paulo, Brazil

Abstract: Swine influenza (SI) is a seasonal infectious disease highly important to the world pig industry. Loss of daily weight gain, increased costs for the prevention and treatment of secondary infections are the main economic losses associated with the presence of this disease. However, some epidemiological features of SI remain quite unclear. This study focused on assessing the prevalence of swine influenza virus (SIV) infection in intensive and extensive pig herds and associating risk factors. A set of 601 blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Here, our study demonstrated exposure of backyard pig populations to IAV with a mean seroprevalence estimated in 5.3% in 2012 and 2.3% in 2014, in which mostly H1N1pdm09 was detected and very few other subtype coinfections were found. This result corroborates a previous study performed in Guatemala, where a high percentage of the pandemic H1 was detected in backyard pig farms, but exposure to swine-origin IAVs from other H1 clades was only found in commercial pig farms showed 24% of seropositive pigs in holdings with intensive production system (Almeida et al, 2017). Similarly, a seroprevalence of 1% was found in backyard pig samples collected in post-pandemic period in Peru (Tinoco et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here, our study demonstrated exposure of backyard pig populations to IAV with a mean seroprevalence estimated in 5.3% in 2012 and 2.3% in 2014, in which mostly H1N1pdm09 was detected and very few other subtype coinfections were found. This result corroborates a previous study performed in Guatemala, where a high percentage of the pandemic H1 was detected in backyard pig farms, but exposure to swine-origin IAVs from other H1 clades was only found in commercial pig farms showed 24% of seropositive pigs in holdings with intensive production system (Almeida et al, 2017). Similarly, a seroprevalence of 1% was found in backyard pig samples collected in post-pandemic period in Peru (Tinoco et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Although it was not possible to collect other biological samples for virus isolation and sequencing to address the genetic background of the circulating IAVs, our results highlight the susceptibility of backyard pig populations to H1N1pdm09, H1N2 and H3N2 viruses. A recent serological study performed in Southeast region in Brazil did not detect IAV seropositivity in pigs from extensive farm system, like the present backyard holdings, but showed 24% of seropositive pigs in holdings with intensive production system (Almeida et al, ). Similarly, a seroprevalence of 1% was found in backyard pig samples collected in post‐pandemic period in Peru (Tinoco et al, ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The husbandry and biosecurity practices adopted by local farms indicate several potential pathways for the introduction of SI into the surveyed farms. For example, live pig movement between pig farms is considered a high-risk practice (Brown, 2000;Almeida et al, 2017) with 57% of the visited farms having introduced live pigs in the year preceding the survey. Approximately one-third (35%) of the farms that introduced pigs in the preceding year did not always quarantine these introduced stock, and of those who did adopt some form of quarantine, half of them only used visual inspection for signs of clinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…Animal influenza is a considerable threat to livestock health, production and welfare (Almeida et al 2017;Vaarst et al 2007). Epidemics also result in human and economic losses, especially in agriculture, public health and tourism.…”
Section: Introductionmentioning
confidence: 99%